Manufacturing industry in Marton : its origins, growth and present nature : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Geography at Massey University - Bertram, David Ian (Massey University, 1970)
Marton can justly claim to be an ideal town for setting up secondary industries......."1 (1)Marton Development Council, n.d., 5. "..... The population over recent years has shown a steady increase and there are signs afoot that the potential of this centrally situated, well planned and solidily supported borough is being realised more and more and that a period of 2 greater industrial development and growth is imminent...."2 (2)Marton Development Council, n.d., 7. ".... The Borough of Marton has the fastest growth rate of any of the towns in the Wanganui Employment District..."3 (3)Marton Development Council, n.d., 7. ".... For its size, Marton must be one of the most prolific factory towns in New Zealand.... "4 (4)Marton Jaycee (Inc.), 1967, 31. ".... Originally the settlement's sole purpose was to service the rich country areas that surround it on all sides, but it has, in recent years, developed into a centre that is above average in industrial development....."5 (5)Young, 1966, 67. Such statements, gleaned from various articles and booklets about the town of Marton, suggest that, in terms of manufacturing industry, it is, in certain respects, atypical of other New Zealand towns of a similar size and has, in fact, considerable potential as a small, industrial centre. The Marton-born writer, too, was aware of certain other distinctive features of the town's manufacturing industry - for example, the virtual absence of industries for processing the produce of its agri-cultural and pastoral hinterland yet the presence of other industries using imported raw materials with markets of nationwide importance.
Keywords: Marton New Zealand; Manufactures